Systematic design of a shower chair: utilization of methods with a participatory approach (Human Factors in Design, 2023)
The abandonment of assistive devices is mostly associated with the disregard for the individual’s needs and the traditionally unsystematic design process. This work presents the systematic and participatory development of the conceptual design of a shower chair. By combining clinical practice instruments and engineering methods, twelve users were interviewed to assist decision-making. The generated solution presented innovation, correspondence with the demands, and good evaluation by health professionals. The approach allowed greater fluidity in the communication between domains, highlighting the heterogeneity within interactions and favoring more objective and egalitarian exchanges.
Keywords: daily living aids; design methodology; customized design